Parkinson's disease-linked DNAJC13 mutation aggravates alpha-synuclein-induced neurotoxicity through perturbation of endosomal trafficking. (3rd January 2018) - Yoshida, Shun; Hasegawa, Takafumi; Suzuki, Mari; Sugeno, Naoto; Kobayashi, Junpei; Ueyama, Morio; Fukuda, Mitsunori; Ido-Fujibayashi, Akemi; Sekiguchi, Kiyotoshi; Ezura, Michinori; Kikuchi, Akio; Baba, Toru; et al.
Abstract: Mutations in DNAJC13 gene have been linked to familial form of Parkinson's disease (PD) with Lewy pathology. DNAJC13 is an endosome-related protein and believed to regulate endosomal membrane trafficking. However, the mechanistic link between DNAJC13 mutation and α-synuclein (αSYN) pathology toward neurodegeneration remains poorly understood. In this study, we showed that PD-linked N855S-mutant DNAJC13 caused αSYN accumulation in the endosomal compartment, presumably due to defective cargo trafficking from the early endosome to the late and/or recycling endosome. In vivo experiments using human αSYN transgenic flies showed that mutant DNAJC13 not only increased the amount of insoluble αSYN in fly head but also induced dopaminergic neurodegeneration, rough eye phenotype and age-dependent locomotor impairment. Together, these findings suggest that DNAJC13 mutation perturbs multi-directional endosomal trafficking, resulting in the aberrant endosomal retention of αSYN, which might predispose to the neurodegenerative process that leads to PD.